The Big Bang: Tax Evasion After Automatic Exchange of Information Under FATCA and CRS. Issue 6 (18th September 2020) - Ahrens, Leo; Bothner, Fabio
ABSTRACT: After decades of ineffective attempts to fight tax evasion, the Foreign Account Tax Compliance Act (FATCA) and the Common Reporting Standard (CRS) recently implemented the first encompassing international exchange of tax-related information on an automatic basis. This is an important development because tax evasion contributes to rising socio-political inequality and political sovereignty losses. This article assesses the treaties' impact on tax evasion by conducting a difference-in-difference analysis of cross-border asset data. The results show that the treaties are successful. Household assets in tax havens that are not hidden behind corporate identities are estimated to be 67 per cent lower than they would have been without automatic exchange of information. Furthermore, this reduction is not offset by an increase in treaty circumvention using identity concealment or asset shifting to non-compliant jurisdictions. FATCA and CRS thus implement the first effective international cooperation against tax evasion. The results imply that political globalisation is capable to mitigate the political sovereignty losses and rise of inequality caused by economic globalisation.